Code-Mixing and Code-Switching in Translation and Interpretation Study - Arsista Yuli Kurniawati; Iin Rachmawati; Chairuddin (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2020)
Language is a combination of several words that have rules in compiling or combining some words into a whole meaning. The relationship between language and society can be called as a sociolinguistics. One of them is code-mixing and code-switching usage. This reserach uses a qualitative research to gets some information about the what, how, when and where of an event occurs or phenomenom. Besides that, the objectives of the research are: (1) to describe the form of code-mixing usage in teaching and learning process on the Seventh semester of the English Department, and (2) to describe the form of code-switching usage in teaching and learning process on the Seventh semester of the English Department.The findings showed that the students used code-mixing and code-switching usage in their presentation process. Firstly, they used code-mixing which consists of 116 forms of the word, 72 forms of the phrase and 1 form of the clause. In the forms of word often used by the students are 16 nouns, 16 adverbs, 12 adjectives, and 12 verbs. Besides that, there are 16 expressions, 12 affixes, and 32 question words usage also in their presentation process. Secondly, they used code-switching which consists of 4 intra-sentential switching and 895 inter-sentential switching. Finally, it can be concluded that in the code-mixing usage, the students are more likely to use the form of the word, while the code-switching usage, they are more likely to use inter-sentential switching.